The Extent to Amount ISIL Acts Against Iraqi Minorities to Genocide - Husein Kokha, Ayad (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2019)
This paper explores the status of Iraq’s most vulnerable people, who have been disproportionately affected by gross human rights violations, and the applicability of the offence of genocide to such violations following the deterioration of the security situation within Iraqi territories under the control of so-called Islamic State of Iraq and the Levant (ISIL). The paper examines the legal concepts of “genocide” and “minority” at the international and internal levels. It identifies heinous acts committed against Iraqi minorities, characterizes the extent to which such acts can be categorized as genocide, and explores the applicable provisions of international criminal law (ICL). The paper employs an analytical-empirical methodology, for it explains the legal texts, accompanied with case law, and compares them with the on-ground status, in addition to data gathering. In terms of the legal context, the paper looks specifically at ICL; in terms of subject, it is restricted to the large-scale killings and other heinous acts perpetrated by ISIL against certain Iraqi minorities, particularly Yazidis, Christians, Turkmans, Kakayis, and Shabaks, that may amount to genocide or other international crimes such as crimes against humanity or war crimes. It is also restricted geographically and chronologically, to certain northern and central areas of Iraq during the period of armed conflict (2014 to 2017) between the Iraqi and Kurdistani governments on the one hand, and ISIL on the other. The main objective of this paper is to study the situation of Iraqi minorities and to monitor grave violations of their rights, specifically regarding the crime of genocide, in order to identify the best legal and judicial measures for intensifying internal and international cooperation in regard to prosecuting perpetrators, implementing the rules of ICL effectively, and eventually protecting these defenceless minorities by avoiding the future recurrence of such crimes.